2022
DOI: 10.3390/v14081799
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Complete Genome Analysis of Porcine Circovirus 2 (PCV2) and an Unclassified CRESS DNA Virus from Diarrheic Pigs in the Dominican Republic: First Evidence for Predominance of PCV2d from the Caribbean Region

Abstract: We report here high rates (47.5%, 48/101) of detection of porcine circovirus 2 (PCV2) in diarrheic pigs from three pig farms in the Dominican Republic. Seventeen of the PCV2 positive samples, representing the three pig farms, different age groups and sampling periods (2020–2021), were amplified for the complete PCV2 genome. Based on analysis of open reading frame 2 and complete genome sequences, the 17 PCV2 strains were assigned to the PCV2d genotype. Significant differences were observed in PCV2 detection rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…On the other hand, co-infections might be due to the widespread occurrence of other major porcine pathogens, such as PCV2, devoid of any association with PCV3 [ 9 , 28 , 33 ]. In previous studies, we screened the 100 porcine fecal samples from the Dominican Republic for PCV2 (detection rates of 48%, 48/100 fecal samples) and porcine adenovirus (PAdV) (26%, 26/100 fecal samples) DNA, and Rotavirus-A (RVA) RNA (0%, 0/100 fecal samples) [ 21 , 34 ]. In the present study, the fecal samples were also screened for the presence of porcine coronaviruses (PDCoV, PEDV, and TGEV) using a pan-coronavirus RT-PCR assay as described previously [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, co-infections might be due to the widespread occurrence of other major porcine pathogens, such as PCV2, devoid of any association with PCV3 [ 9 , 28 , 33 ]. In previous studies, we screened the 100 porcine fecal samples from the Dominican Republic for PCV2 (detection rates of 48%, 48/100 fecal samples) and porcine adenovirus (PAdV) (26%, 26/100 fecal samples) DNA, and Rotavirus-A (RVA) RNA (0%, 0/100 fecal samples) [ 21 , 34 ]. In the present study, the fecal samples were also screened for the presence of porcine coronaviruses (PDCoV, PEDV, and TGEV) using a pan-coronavirus RT-PCR assay as described previously [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The present study was based on archival fecal samples that were obtained from 100 diarrheic pigs for a previous research project on porcine enteric viruses (PCV2, PAdV, and RVA) in the Dominican Republic [ 21 ]. During August-November 2020, 34 and 16 fecal samples were obtained from diarrheic pigs at a farm in the municipality of Cabrera (housing ~300 pigs) and Pedro Brand (~100 pigs), respectively, and in January–February 2021, 50 fecal samples were collected from a pig farm in the municipality of Villa Mella (~500 pigs) ( Supplementary Figure S1 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown a shift in the most prevalent genotypes in pig production over the years [17] from the PCV2a genotype to PCV2b in 2002 [48], [49], and in 2012, a shift occurred from PCV2b to PCV2d [34], [50]. Since then, PCV2d has become the most prevalent in various regions of the world, such as China [37], South Korea [51], Austria [42], the United States [13], Colombia [52], and the Dominican Republic [53].…”
Section: Discussionmentioning
confidence: 99%